Comparative Analysis of Full Outline of Unresponsive Score and Glasgow Coma Scale Score for Outcomes Prediction in Children with Impaired Consciousness - Gaur, Bablu Kumar; Meman, Mohamad Habib F.; Jain, Shruti (Neuropediatrics, 2025)
This study aimed to compare two distinct consciousness evaluation scores (the pediatric Glasgow coma scale [GCS] scale and the full outline of unresponsive [FOUR] score) to predict outcomes for children admitted to the pediatric intensive care unit with impaired consciousness.Children aged between 2 and 18 years who presented with impaired consciousness were included in this longitudinal study. The lead investigator evaluated the pediatric GCS score and the FOUR score. The first 3 days' score readings of both the scores were taken for analysis. The primary outcome of children was recorded as in-hospital mortality. The secondary outcome was functional outcome measured by the modified Rankin scale.A total of 78 children presented with impaired consciousness were eligible for statistical analysis. Survivors and nonsurvivors had significantly different FOUR and GCS scores at admission, 24 and 48 hours (p < 0.0001). The predictive accuracy of the FOUR scale at admission was slightly higher than GCS considering that the area under the curve (AUC) for the FOUR score was higher (AUC = 0.850; 95% confidence interval [CI]: 0.735–0.956) than GCS (AUC = 0.834; 95% CI: 0.735–0.934). The projected outcome based on the FOUR score and the actual patient outcomes were statistically significantly correlated (p = 0.021). Results showed that the FOUR scores had higher sensitivity (89%) specificity (84%), and negative predictive value (83%) than the GSC scale.The FOUR at admission was a better predictor of the outcome as compared with the Glasgow coma scale. More sensitivity of the FOUR scores than GCS makes it an advisable predictive model for children with impaired consciousness.
Keywords: impaired consciousness; GCS score; FOUR score; outcome; children